266 Effects of Inflammatory States on Ovarian Biology and Oocyte Competence. (8th October 2021) - Hernandez Gifford, Jennifer A; Ferranti, Emily; Forrest, Kylee; Gifford, Craig A
Abstract: Female fertility is dependent on estradiol concentrations which regulate a multitude of ovarian functions including follicle development and oocyte maturation leading to ovulation of a viable oocyte. Estradiol biosynthesis is regulated by coordinated actions of follicle-stimulating hormone and intra-ovarian control mechanisms including the co-transcription factor beta-catenin. Beta-catenin is a multi-faceted protein recognized for its role in granulosa cell steroid production and is shown to be modulated by lipopolysaccharide (LPS), the endotoxin responsible for stimulation of the immune system in infections caused by Gram-negative bacteria. Beef heifers treated with subacute concentrations of LPS during a synchronized follicular wave demonstrate a decline in serum estradiol concentrations 50 h after CIDR withdrawal, corresponding with dominant follicle maturation and preceding ovulation. The endotoxin exposure also resulted in increased LPS concentration and E2 :P4 ratios in follicular fluid suggesting that low dose LPS modulates the intra-follicular hormonal milieu. Additionally, in a granulosa cell line, LPS treatment decreased mRNA expression of aromatase and beta-catenin. These data indicate that LPS alters E2 synthesis by modulating beta-catenin and subsequent steroidogenic enzyme expression. To further explore the contribution of naturally occurring LPS exposure on follicular steroid production and developing oocytes, bovine ovary pairs were collected from local abattoirs. Oocytes were aspirated from small follicles and matured in vitro to evaluate meiotic events related to nuclear maturation and spindle morphology. Small follicles from ovarian pairs were separated by the detectable LPS concentrations into high and low LPS groups. Oocytes matured from low LPS follicles demonstrated an increase in the percent of abnormal maturation events. Data indicate that induced or naturally occurring low doses of LPS can alter circulating and follicular estradiol concentrations impairing oocyte maturation. Perturbation to local ovarian signaling cascades from subclinical inflammatory disease may be an unappreciated factor altering fertility and leading to decreased cow retention.